An Analysis of the Educational Administration and Finance after the Publication of the Report of National Council on Educational Reform : Focusing on the Immortal Resources and the Problem of the Derivation of the Resources(<Special Issue>State Responsibilities on Education and Decentralization : Considering Transformation of "School") - TAKAMI, Shigeru (THE JAPANESE JOURNAL OF EDUCATIONAL RESEARCH, 2004)
In this thesis, I tried to clarify the relationship between the resource management of the public sector and the state of "Governance" by following the outline of the education policy after the publication of the report of the National Council on Educational Reform. The education sector has been burden with the fixed cost such as capital investment or personnel expenses. Therefore, under the financial crisis, it becomes one of the most important policy problems for the public sector how to do with the management of education resources. The criterion of the allocation policy of the education resources can be generalized as follows, that is to say, i) saving the consume of the resources which become extinct by making use of the outside resources (the derivation of the resources), ii) giving priority to use immortal resources. These policy lines are observed in constructing the schoolhouse by PFI (Private Finance Initiative) scheme or introducing the outsourcing of school management. Recently it is highly noticed as a useful policy means to introduce the immortal resources into the school management in order to allocate the education resources. But we cannot find out the sphere of the business activities of private companies in PFI scheme, and the extent of the outsourcing to private sector. In other words there is no evidence to show the rational extent of derivation of the outside resources. Therefore, I implemented the questionnaires to private companies and tried to find out the rational extent of deviation of resources. The following procedure is adopted; first of all the school management was classified into ten fields (school affairs, instruction of subjects, guidance of course, counseling, teacher training, general affairs and accounting, management of facilities and expendable supplies, management of the school library, school events and ceremony, school lunch and transportation), then the private companies were questioned how far can they entry into them and undertake a job on behalf of public sector. Through out a cluster analysis, which was implemented based on the data, the school management sector was classified into two parts. They are the "core part" and the "non core part". The former fits instruction or guidance, and the latter has the function to support the former around it. It is very hard to derivate the resources from the outside into the former because of the conflict with professionalism. The other side newly discovered that that the derivation of the outside resources into the latter is comparatively practical. There are some points concerning the derivation of resources; that is i) how to correspond to the decline in disciplinary school management, ii) how to conquer the limitations of the resource derivation power.